“Determinación del costo de producción de la actividad de tostado del café tradicional de la empresa “Indera Experience” en el periodo 01 de abril al 30 de junio 2024” - Ruiz Nole, Wilmer José (2025)
The present Work of Curricular Integration called “Determination of the production cost of the activity of roasting traditional coffee of the company ‘Indera Experience’ in the period April 01 to June 30, 2024” was carried out with the purpose of knowing the production cost of the elaboration of traditional coffee, information that will be of much importance for the company, to improve and to be able to identify in a better way the costs incurred in the production, helping to obtain better results in the control and registration of the costs that incur to get to determine the total cost of each production as well as the real unit cost, allowing to obtain a good profitability. The methodology used is descriptive in nature, since it is based on the collection of information through the application of an interview with the owner of the company “Indera Experience” where the lack of knowledge of the costs incurred and the control of these costs when obtaining the finished product was identified. In order to achieve the determined objectives, flow charts, procedures and implementation of policies in relation to the production of coffee were developed, as well as the respective auxiliary documents such as purchase request, purchase order, production order, requisition order, time cards, clock cards, payment role, cost sheet, indirect manufacturing costs budget, kardex cards, which allowed us to keep good control and record of raw material, labor and indirect manufacturing costs, cost sheet, indirect manufacturing cost budget, kardex cards, which allowed us to keep a good control and record of the raw material, labor and indirect manufacturing costs, which were used to obtain the total and unit cost of each production in the process of transformation of the raw material to the finished product. Likewise, the accounting process was executed from the preparation of the chart of accounts, accounts manual, initial inventory, initial situation statement, journal, general ledger and statement of cost of products sold where it shows us an actual cost of $14,920.11 for the three months of production, grouping the three cost elements.